Studi Literatur Potensi dan Perkembangan Teknik Ekstraksi Minyak Alpukat - Rahmah Humairah; Ryan Moulana; Yanti Meldasari Lubis; Amrina Maulida; Dina Annisa; Satriana (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The high production of avocados has driven the diversification of this commodity, such as as an alternative raw material for the production of vegetable oil, namely avocado oil. To produce products with better quality and efficiency, development is needed in one of the processes, such as the extraction stage. The discussion in this literature review includes the potential and development of extraction techniques such as cold-pressed extraction, leaching, microwave-assisted extraction/MAE and solvent extraction to maximize avocado oil production. Through a comprehensive analysis, this study aims to provide a better understanding of how these processes affect the characteristics and quality of avocado oil. The results of this study are expected to provide guidance for avocado oil producers and researchers in developing better avocado oil processing techniques, so that the economic potential and sustainability of avocado oil can be optimized.